Labour precarity among maids. The case of 3-4 star hotels in Villa de Merlo, San Luis, Argentina - Mateucci, María Azul (2025)
The purpose of this article is to present the current status of working conditions for maids in 3- and 4-star hotels in Merlo, San Luis, in 2022, based on research conducted. It examined aspects related to labour legislation, work experience, work organisation, and occupational health through surveys of maids using both closed and openended questions, to obtain statistically comparable information. The study also includes a comparison with the current evolution of working conditions. The analysis highlighted the need to address the conditions under which this employment is carried out, which significantly impact the workers’ lives.